Выражение 9(2у-1)-2(5+-8) решите уравнение -2(2-5х)=2(х-3)-5 -(3у+7)=8-2(8-у) 4х-2(х+7)=2(3-х)

dapmoney2p0c8c0 dapmoney2p0c8c0    1   29.03.2019 16:40    0

Ответы
elisavetto4ka elisavetto4ka  27.05.2020 13:26

9(2y-1)-2(5+3y)-(y-8)

18y-9-10-6y-y+8

11y-11

 

-2(2-5x)=2(x-3)-5

-4+10x=2x-6-5

10x-2x=-6-5+4

8x= -7

x= -7/8

 

-(3y+7)=8-2(8-y)

-3y-7=8-16+2y

-3y-2y=8-16+7

-5y= -1

y=1/5

 

4x -2(x+7)=2(3-x)

4x-2x-14=6-2x

2x-14=6-2x

2x+2x=6+14

4x=20

x=5

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика